Concentrations of Selected Trace Metals in Groundwater from a Legacy oil-spill location in Rivers State, Nigeria - Austin, Sokpuwu; Udousoro, Imaobong (Covenant Journal of Physical and Life Sciences, 2021)
This study was carried out to assess the concentrations of some selected trace metals in borehole water from a legacy oil spill location in Rivers State, Nigeria. Water samples were collected from ten (10) functional boreholes using standard techniques. The levels of the trace metals in the study area were found to be in the order of: cadmium (0.361±0.381 mg/L), > lead (0.117±0.056 mg/L) > nickel (0.042±0.0281 mg/L) > cobalt (0.010±0.009 mg/L) in the water samples. These values were above the WHO and NIS limits. The water quality parameters varied across the sampling periods (June and August); apart from Cd whose mean value was higher during the month of June, but lower during the second month. The groundwater from the community is therefore, unsafe for drinking purpose due to elevated levels of toxic metals. These findings give cause of concern, particularly as trace metals are bio accumulative in the human system and portends a serious health risk to man. In light of these findings, periodic analysis of samples from boreholes is inevitable so as to reveal contamination or pollution status of groundwater in this area and to determine the best method for water treatment. It will help in safeguarding the health of water consumers against the subsequent impact that may arise from drinking trace metals contaminated water